2021
DOI: 10.3390/act10040079
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a 2-DOF Active Magnetic Bearing Actuator for Unmanned Underwater Vehicle Thruster Application

Abstract: In this work, a novel application of Active Magnetic Bearing (AMB) is proposed to integrate AMB in the Magnetically Coupled Thruster (MCT) assembly for underwater application. In this study, a 2-Degree-Of-Freedom (DOF) AMB is developed and investigated for the MCT of an Unmanned Underwater Vehicle (UUV). The paper presents the detailed electro-mechanical modeling of the in-house developed AMB system. The intractable problem of rotor suspension and rotation with opposing pairs of electromagnets is considered. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…It is also crucial to apply magnetic bearings to the centrifugal axle shaft system and turbines as this will not cause pollutants. Magnetic bearings do not require lubrication, nor do they touch the centrifugal axle shaft (zero touch) [66,75]. A firm in Japan and the United States suggested that the installation of magnetic bearings to compressor technology of centrifugal chillers can save costs up to 42.3-50%/year [76][77][78].…”
Section: Efficiency Comparison Of N 2 Generator and With Injection Steam Turbine Enginementioning
confidence: 99%
“…It is also crucial to apply magnetic bearings to the centrifugal axle shaft system and turbines as this will not cause pollutants. Magnetic bearings do not require lubrication, nor do they touch the centrifugal axle shaft (zero touch) [66,75]. A firm in Japan and the United States suggested that the installation of magnetic bearings to compressor technology of centrifugal chillers can save costs up to 42.3-50%/year [76][77][78].…”
Section: Efficiency Comparison Of N 2 Generator and With Injection Steam Turbine Enginementioning
confidence: 99%
“…The magnetic support system of a high-speed machine rotor usually consists of an electromechanical actuator, a control unit, amplifiers and sensors [ 15 , 16 , 17 , 18 , 19 , 20 ]. The electromechanical actuator is intended to support a high-speed rotor and generate electromagnetic force, providing its stable operation.…”
Section: Introductionmentioning
confidence: 99%
“…Two types of sensors are typically used in the AMB systems, namely induction sensors and displacement sensors. Induction sensors have good potential but are difficult to use because they must be mounted in the bearing air gap [ 17 , 18 ]. On the other hand, displacement sensors are more expensive and introduce some design limitations, but their configuration and assembly are simpler than in the case of induction sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Modeling is developed to understand collective behaviors in nature better, as well as to effectively control artificial swarms, such as multi-robot systems [8] and unmanned vehicles [9][10][11]. Reynolds proposed the Boid model and ran the first computer simulation of flocking based on three heuristic rules, known as cohesion, separation, and alignment [12].…”
Section: Introductionmentioning
confidence: 99%